2023
DOI: 10.1002/mnfr.202200847
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between APOE, APOA1, and LPL Gene Polymorphisms and Variability in Changes in Lipid and Blood Pressure following Orange Juice Intake: A Pilot Study

Abstract: Scope Chronic orange juice intake is associated with reduced risk of cardiovascular disease, however, a large inter‐individual variability in response to orange juice for lipid profile and blood pressure has been observed. This heterogeneity in responsiveness could be associated with single nucleotide polymorphism (SNP), which has not been previously addressed. This study aims to investigate the influence of SNP in apolipoprotein E (APOE), apolipoprotein A1 (APOA1), mevalonate (MVK), and lipase lipoprotein (LP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…This study revealed that individuals with greater GRS present high blood pressure associated with higher coffee consumption, highlighting the particular importance of reducing coffee intake in individuals who are genetically predisposed to this cardiovascular disease risk factor [66]. Moreover, polymorphisms in LPL and APOE genes were suggested to modulate the effects of orange juice rich in flavanone on vascular function [20]. Taken together, these examples strongly suggest that the candidate genes identified using our integrative analyses of genomic and GWAS data are good candidates, demonstrating the power of such an approach for the identification of novel, still unexplored candidate genes involved in interindividual variability in response to flavonoid intake and vascular health.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…This study revealed that individuals with greater GRS present high blood pressure associated with higher coffee consumption, highlighting the particular importance of reducing coffee intake in individuals who are genetically predisposed to this cardiovascular disease risk factor [66]. Moreover, polymorphisms in LPL and APOE genes were suggested to modulate the effects of orange juice rich in flavanone on vascular function [20]. Taken together, these examples strongly suggest that the candidate genes identified using our integrative analyses of genomic and GWAS data are good candidates, demonstrating the power of such an approach for the identification of novel, still unexplored candidate genes involved in interindividual variability in response to flavonoid intake and vascular health.…”
Section: Discussionmentioning
confidence: 82%
“…In the study group of 46 participants, medium or high excretors of flavanone metabolites, it was observed that for the APOA1_rs964184 polymorphism, the CC genotype is associated with a decrease in circulating triglycerides and blood pressure, both systolic and diastolic. Additionally, for the LPL_rs12678919 polymorphism, the AA genotype was associated with a change in blood lipids [20].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation